Development of a novel electronic neonatal nutrition assessment tool. (24th May 2012) - Johnson, MJ; Schofield, J; Pearson, F; Emm, A; Leaf, AA
Abstract : Background: Poor growth is common in preterm infants in the neonatal period, with poor weight gain, short stature and altered body composition when compared to term infants. Achieving recommended nutrient intakes is difficult; however it is not easy to demonstrate this contemporaneously in routine clinical practice. Methods: We developed a customised electronic tool (SENNAT) to capture and analyse growth and nutritional data, with the aim of gaining better understanding of neonatal nutrition at individual and population level. SENNAT uses pre-loaded information on the nutritional content of feeds and fluids to calculate an individual's total daily nutrient intake from daily fluid volumes, and compares these to current recommendations (Tsang 2005). Graphical reports are produced to aid clinical decisions. SENNAT was used to carry out a retrospective review of all infants with a birth weight <1500 g or gestational age at birth <30 weeks, in-born during 2009. Results: From 70 eligible infants, case notes were available for 64. Intakes of selected nutrients compared to recommendations for the first week of life through to 36 weeks post conceptual age (PCA) are shown in table 1, together with standard deviation scores (SDS) for weight and head circumference. Figures are mean (SD). Conclusions: Patterns of nutrient intake changed, reflecting periods on parental nutrition, transition to milk feeds and use of nutritional supplements. Intakes of protein were low throughout stay, whilst micronutrient intakes varied. At 36 weeks PCA most intakes were below recommended values and this was reflected in poor growth. We anticipate that modifications to our nutrition policy, combined with weekly assessment using SENNAT, will result in improved nutrient intakes and growth during prospective study in 2012.